Principles of pavement engineering - Thom, Nick (ICE Publishing, 2014)
This edition builds on the previous edition, expanding on the fundamental principles of pavement engineering, concentrating on an understanding of the behaviour of pavement materials and of the real meaning of tests carried out on those materials. It includes necessary updates, such as: warm-mix asphalt, as it is increasingly environmentally attractive; cold-mix asphalt; asphalt recycling; bridge deck surfacing; design against potholes; treatment of Stress Absorbing Membrane Interlayers; surface treatments; pavement edge issues; and parking areas. This book also covers soils, granular materials and hydraulically-bound materials (including concrete), and will explain the various relevant engineering properties of those materials and how they are affected by such matters as compaction, water content, binder content and more.
Formerly CIP.
Keywords: Pavements -- Design and construction.; Pavements -- Maintenance and repair.; Road materials.; elektronické knihy; electronic books